2015
DOI: 10.1038/ncomms8324
|View full text |Cite
|
Sign up to set email alerts
|

WASH and Tsg101/ALIX-dependent diversion of stress-internalized EGFR from the canonical endocytic pathway

Abstract: Stress exposure triggers ligand-independent EGF receptor (EGFR) endocytosis, but its post-endocytic fate and role in regulating signalling are unclear. We show that the p38 MAP kinase-dependent, EGFR tyrosine kinase (TK)-independent EGFR internalization induced by ultraviolet light C (UVC) or the cancer therapeutic cisplatin, is followed by diversion from the canonical endocytic pathway. Instead of lysosomal degradation or plasma membrane recycling, EGFR accumulates in a subset of LBPA-rich perinuclear multive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
91
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 43 publications
11
91
2
Order By: Relevance
“…Therefore, low-EGF and TNF- appear to drive a common endocytosis/recycling system under the control of p38 activation. A recent study reported that cellular stresses, including ultraviolet C (UVC) and the genotoxic agent cisplatin, trigger sustained p38 activation and the non-canonical endocytosis of EGFR, in which EGFR accumulates in a subset of lysobisphosphatidic acid (LBPA)-rich perinuclear MVBs through a mechanism involving the actin polymerization-promoting protein WASH and endosomal sorting complex containing ALIX and ESCRT (30). The inhibition of p38 results in the recycling of intraluminally sorted EGFR to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, low-EGF and TNF- appear to drive a common endocytosis/recycling system under the control of p38 activation. A recent study reported that cellular stresses, including ultraviolet C (UVC) and the genotoxic agent cisplatin, trigger sustained p38 activation and the non-canonical endocytosis of EGFR, in which EGFR accumulates in a subset of lysobisphosphatidic acid (LBPA)-rich perinuclear MVBs through a mechanism involving the actin polymerization-promoting protein WASH and endosomal sorting complex containing ALIX and ESCRT (30). The inhibition of p38 results in the recycling of intraluminally sorted EGFR to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR endocytic trafficking is involved in different cellular responses (29). It is essential to investigate the role of the MAPK-dependent non-canonical regulation of EGFR in the initiation of autophagy in cisplatin-treated cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In early endosomes, stress-exposed EGFR is sorted away from its ligandstimulated counterpart into a distinct population of relatively stable MVBs where they accumulate on both the ILVs and the MVB limiting membrane. Segregation of ligand-stimulated and stressinduced EGFR in early endosomes is orchestrated by the WASH complex, 1 presumably involving its actin polymerisation-driven endosomal subdomain specification properties. 4 Analysis of exogenously-expressed potential cargoes that might accompany stress-exposed EGFR into this particular subtype of MVB lead us to conclude that these MVBs represent endosomal precursors to lysosome-related organelles, such as melanosomes.…”
Section: Stress Reveals New Destination For Egf Receptormentioning
confidence: 99%
“…Surprisingly, and contrary to receptor activity following ligand binding, EGFR activation does not occur if internalisation from the plasma membrane is abrogated. 1 As maintenance of signaling is enabled by the ALIX-driven sequestration of stress-exposed EGFR in MVBs, 1 we hypothesize that repeated rounds of ESCRT and ALIX-dependent internalisation and back-fusion of EGFR to and from ILVs ensures continued accessibility of the receptor to downstream signaling molecules. This hypothesis is reinforced by the previously suggested role of ALIX in ILV back-fusion events during nucleocapsid release to the cytosol from endosomes in the process of viral infection.…”
Section: Stress Reveals New Destination For Egf Receptormentioning
confidence: 99%
See 1 more Smart Citation